2015
DOI: 10.1071/rd13144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pathogenic bacteria species present in the postpartum bovine uterus on proteome profiles

Abstract: Abstract. In the first 2-3 weeks after parturition .90% of dairy cows will have some form of uterine infection. Uterine contamination with pathogens, such as Trueperella (formerly Arcanobacterium) pyogenes increases the risk of developing more severe endometritis, which can reduce conception rates. In this study, we compared the uterine proteome of cows infected with Trueperella pyogenes with that of uninfected cows, using 2D gel electrophoresis, and identified annexins A1 and A2 (ANXA1 and ANXA2), apolipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…In cattle, XBP1 is involved in corpus luteum development and maintenance [53], and is upregulated in large follicles [54]. Window 18-19Mb of BTA26 harbors FRAT1 which is differentially expressed during the secretory phases of the human endometrium [55], and PGAM1 related to spermatogenesis success in mice [56] whose expression was found to be increased in cows with postpartum infection caused by pathogenic bacteria [57]. …”
Section: Resultsmentioning
confidence: 99%
“…In cattle, XBP1 is involved in corpus luteum development and maintenance [53], and is upregulated in large follicles [54]. Window 18-19Mb of BTA26 harbors FRAT1 which is differentially expressed during the secretory phases of the human endometrium [55], and PGAM1 related to spermatogenesis success in mice [56] whose expression was found to be increased in cows with postpartum infection caused by pathogenic bacteria [57]. …”
Section: Resultsmentioning
confidence: 99%
“…and T. pyogenes were the most common. Isolation of E. coli at 0 DIM did not have an effect at 21 DIM on the isolation of T. pyogenes but T. pyogenes was associated with PVD (de-Boer et al, 2015;Ledgard et al, 2015).…”
Section: Infectious Factorsmentioning
confidence: 77%
“…Some proteins have been correlated with the percentages of PMN as well. Ledgard et al (2015) found a strong correlation between percentages of PMN and cathelicidin, PGLYRP1, SERPINB1, and S100A9. These proteins are products of immune cells in response to a current infection and during a prolonged inflammatory response.…”
Section: Diagnosis Of Uterine Diseasementioning
confidence: 78%
See 2 more Smart Citations